Cardioprotection against experimental myocardial ischemic injury using cornin - Xu,Y. (2016)
Phosphorylated-cyclic adenosine monophosphate response element-binding protein (Phospho-CREB) has an important role in the pathogenesis of myocardial ischemia. We isolated the iridoid glycoside cornin from the fruit of Verbena officinalis L, investigated its effects against myocardial ischemia and reperfusion (I/R) injury in vivo, and elucidated its potential mechanism in vitro. Effects of cornin on cell viability, as well as expression of phospho-CREB and phospho-Akt in hypoxic H9c2 cells in vitro, and myocardial I/R injury in vivo, were investigated. Cornin attenuated hypoxia-induced cytotoxicity significantly in H9c2 cells in a concentration-dependent manner. Treatment of H9c2 cells with cornin (10 µM) blocked the reduction of expression of phospho-CREB and phospho-Akt in a hypoxic condition. Treatment of rats with cornin (30 mg/kg, iv) protected them from myocardial I/R injury as indicated by a decrease in infarct volume, improvement in hemodynamics, and reduction of severity of myocardial damage. Cornin treatment also attenuated the reduction of expression of phospho-CREB and phospho-Akt in ischemic myocardial tissue. These data suggest that cornin exerts protective effects due to an increase in expression of phospho-CREB and phospho-Akt.